The Heparan Sulfate Sulfotransferases HS2ST1 and HS3ST2 Are Novel Regulators of Breast Cancer Stem-Cell Properties - Teixeira, Felipe C. O. B.; Vijaya Kumar, Archana; Kumar Katakam, Sampath; Cocola, Cinzia; Pelucchi, Paride; Graf, Monika; Kiesel, Ludwig; Reinbold, Rolland; Pavão, Mauro S. G.; Greve, Burkhard; Götte, Martin (Frontiers in Cell and Developmental Biology, 2020)
Heparan sulfate (HS) is a glycosaminoglycan found mainly in its protein-conjugated form at the cell surface and the extracellular matrix. Its high sulfation degree mediates functional interactions with positively charged amino acids in proteins. 2-O sulfation of iduronic acid and 3-O sulfation of glucosamine in HS are mediated by the sulfotransferases HS2ST and HS3ST, respectively, which are dysregulated in several cancers. Both sulfotransferases regulate breast cancer cell viability and invasion, but their role in cancer stem cells (CSCs) is unknown. Breast CSCs express characteristic markers such as CD44+/CD24-/low, CD133 and ALDH1 and are involved in tumor initiation, formation, and recurrence. We studied the influence of HS2ST1 and HS3ST2 overexpression on the CSC phenotype in breast cancer cell lines representative of the triple-negative (MDA-MB-231) and hormone-receptor positive subtype (MCF-7). The CD44+/CD24-/low phenotype was significantly reduced in MDA-MB-231 cells after overexpression of both enzymes, remaining unaltered in MCF-7 cells. ALDH1 activity was increased after HS2ST1 and HS3ST2 overexpression in MDA-MB-231 cells and reduced after HS2ST1 overexpression in MCF-7 cells. Colony and spheroid formation were increased after HS2ST1 and HS3ST2 overexpression in MCF-7 cells. Moreover, MDA-MB-231 cells overexpressing HS2ST1 formed more colonies and could not generate spheres. The phenotypic changes were associated with complex changes in the expression of the stemness-associated notch and Wnt-signaling pathways constituents, syndecans, heparanase and Sulf1. The results improve our understanding of BCSC function and mark a subtype-specific impact of HS modifications on the CSC phenotype of triple-negative and hormone receptor positive breast cancer model cell lines.